Chili pepper as a body weight-loss food*. (19th May 2017) - Varghese, Sharon; Kubatka, Peter; Rodrigo, Luis; Gazdikova, Katarina; Caprnda, Martin; Fedotova, Julia; Zulli, Anthony; Kruzliak, Peter; Büsselberg, Dietrich
Abstract: Chili has culinary as well as medical importance. Studies in humans, using a wide range of doses of chili intake (varying from a single meal to a continuous uptake for up to 12 weeks), concluded that it facilitates weight loss. In regard to this, the main targets of chili are fat metabolism, energy expenditure, and thermogenesis. To induce weight loss, the active substance of chili, capsaicin, activates Transient Receptor Potential Cation Channel sub-family V member 1 (TRPV1) channels) receptors causing an increase in intracellular calcium levels and triggering the sympathetic nervous system. Apart from TRPV1, chili directly reduces energy expenditure by activating Brown Adipose Tissue. Weight loss by chili is also the result of an improved control of insulin, which supports weight management and has positive effects for treatment for diseases like obesity, diabetes and cardiovascular disorders. This review summarizes the major pathways by which chili contributes to ameliorating parameters that help weight management and how the consumption of chili can help in accelerating weight loss through dietary modifications.